Analisis Kelayakan Protocol Rounting Open Shortest Path First (OSPF) Pada Topologi Tree Dengan Simulator Cisco Packet Tracer - Lelis Reminis There Gulo; Ardiansyah Ardiansyah; Yuninda Triyatne; Muhammad Ziddan Al fariz; Didik Aribowo (Universitas Katolik Widya Karya Malang, 2024)
This study aims to analyze the performance of the OSPF routing protocol in a tree topology using the Cisco Packet Tracer simulator with a router configuration, and a PC/computer. This research involves building a tree topology consisting of several router nodes and PC/computers, where OSPF is implemented to manage routing. Tests were conducted using steady ping on PC to PC, PC to router and PC to server to measure network performance in terms of latency and reliability. The test data was analyzed to evaluate OSPF convergence, network stability and rounting efficiency. The results of this study provide insight into the effectiveness of OSPF in a tree topology.